Potential C-terminal domain interactions of the cardiac voltage gated sodium channel - Spencer K. Lile; Emily M. Campbell; Rita F. Gyawu; Jarrod A. Smith; Steven R. Gwaltney; Christopher N. Johnson (Scientific Reports)
Abstract CryoEM structural characterization of the cardiac sodium channel (NaV1.5) captured the cytosolic C-terminal domain (CTD) interacting with the cytosolic loop that connects domains III and IV (inactivation gate). Our previous modeling efforts focused on improving descriptions of the cytosolic components and unexpectedly captured dissociation of this complex. Other reports have provided evidence of CTD interaction with a different cytosolic NaV1.5 component. Specifically, NMR spectroscopy demonstrated that a reconstituted CTD (93 amino acids construct, helices I–IV) could engage a peptide corresponding to an IQ motif (helix VI) that is also contained on the C-terminus of the NaV1.5 channel. Here, we leverage recent MD simulation advancements to expand upon this work and investigate the potential of the CTD–IQ motif interaction within the context of a full-length sodium channel imbedded within a lipid bilayer. Four independent one microsecond simulations (with explicit lipids, salts, and water) depicted a stable CTD–IQ motif complex for the duration of each simulation. An additional four independent one microsecond simulations of the CTD molecule dissociated from both the inactivation gate and IQ motif failed to capture an association event, suggesting the existence of at least three CTD energetic minima within the context of the full-length alpha subunit.